Development of Technoprenuer Education and Training Model through Internet of Things (IoT) Based Smart Transportation System Application for UPI Students - Muhammad Adli Rizqulloh; Hasbullah Hasbullah; Bachtiar Hasan; Neris Peri Ardiansyah (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
Technology-based entrepreneurial (Technoprenuer) trainings aim at increasing the interest of students and university graduates to become Technoprenuer actors as part of reducing the number of educated unemployment rate. On the other hand, based on the continuously development of transportation technology, smart transportation utilizing the Internet of Things (IoT) is expected to help many parties in the field of supervision and enforcementas as well as the community as it can improve safety and reduce the level of accidents on the road. Therefore, this training provided material on technoprenership and IoT implementation to gain those two benefits. The training was held for 2 weeks, 2 days of which were synchronous and the rest were asynchronous. The trainees consisted of 15 UPI students and they were expected to be able to build prototypes in the end of the training. As the result, 60% of the participants were able to realize their business ideas until the prototype stage.